Impact of Risk Governance Practices on Financial Performance of Listed Banks, Finance Companies and Insurance Companies in Sri Lanka - Ramasinghe, D.S.E.; Kawshalya, M.D.P. (Department of Accountancy, Faculty of Commerce and Management Studies, University of Kelaniya, 2020)
This study investigates the impact of risk governance practices on financial performance of listed banks, finance and insurance companies in Sri Lanka. Basically, when considering the performances of banks, finance and insurance companies, they will have to make changes to their risk governance to guide all employees and teams to achieve specific targets and increase their profitability. Even though these companies have to pay more attention on the risk governance practices for an effective progress, there were some cases in Sri Lanka that had unfortunate track records as some of those institutes have been collapsed which led the society suffer the whole economy. This study aims to provide an original insight into risk governance variables that affect the financial performance of listed banks, finance and insurance companies of Sri Lanka by analysing the risk governance practices and to which extent those risk governance practices have made an impact to financial performance. Sample of the study is selected as the 71 companies from the sectors, banks (10), finance companies (49) and insurance companies (12). Since the independent variable of this study is “risk governance”, to measure the variable researcher has used an already developed comprehensive Risk Governance Index (RGI) by Mostafa Kamal Hassan (2009). This study will carry significant importance for risk managers, bank executives, regulatory authorities, policy makers and future researchers. Specially when analysing developing tools for banks, finance companies and insurance companies this study will be more of use to help management discern difficultto-see risks and to improve response speed of their financial performance.
Keywords: Colombo Stock Exchange, Financial Performance, Risk Governance, Risk Governance Index, Sri Lanka